Research on a New Circuit of Temperature Measurement - Zhixiang Zeng; Xuanze Wang; Liangen Yang; Yuning Zhong; Zhongsheng Zhai (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Temperature measurement is an important link in industrial production, also an important part of modern testing technology. The traditional single bridge circuit is already unable to meet the requirements of modern precise temperature measurement system on temperature measurement. The relation between the output voltage of general Wheatstone bridge and real strain is nonlinear. The nonlinear error will be very serious if the variance ratio of resistance ΔR/ R is very large. Platinum resistance temperature sensor as temperature element may also cause nonlinear error.And measuring ranges small for bridge. This paper designs RC filter circuit and second-order band-pass filter circuit as the core of a new type of temperature measurement circuit ,introduces the principle of temperature measurement and the generation of signal source .Circuit cooperates with thermistor sensor, not only realizes the high precise temperature measurement, but also solves the measurement error of sensor produced from heating. Experiment checks that measuring precision can satisfy measurement requirements. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3105